Systemic blood pressure in severe aortic stenosis: Haemodynamic correlates and long‐term prognostic impact. (7th October 2022) - Maeder, Micha T.; Rickli, Hans; Weber, Lukas; Weilenmann, Daniel; Ammann, Peter; Joerg, Lucas; Haager, Philipp K.; Rigger, Johannes; Chronis, Joannis; Brenner, Roman
Abstract: Aims: Blood pressure (BP) targets in patients with aortic stenosis (AS) are controversial. This study sought to describe the haemodynamic profile and the clinical outcome of severe AS patients with low versus high central meaarterial pressure (MAP). Methods and results: Patients with severe AS ( n  = 477) underwent right and left heart catheterization prior to aortic valve replacement (AVR). The population was divided into MAP quartiles. The mean systolic BP, diastolic BP, and MAP in the entire population were 149 ± 25, 68 ± 11, and 98 ± 14 mmHg. Patients in the lowest MAP quartile had the lowest left ventricular ejection fraction (LVEF), systemic vascular resistance, and valvulo‐arterial impedance, whereas there were no significant differences in mean right atrial pressure, mean pulmonary artery wedge pressure, pulmonary vascular resistance, and stroke volume index across MAP quartiles. However, left ventricular stroke work index (LVSWI) was lowest in patients in the lowest and highest in those in the highest MAP quartile. After a median (interquartile range) post‐AVR follow‐up of 3.7 (2.6–5.2) years, mortality was highest in patients in the lowest MAP quartile [hazard ratio 3.08 (95% confidence interval 1.21–7.83); P  = 0.02 for lowest versus highest quartile]. In the multivariate analysis, lower MAP [hazard ratio 0.78 (95% confidence interval 0.62–0.99) per 10 mmHg increase; P  = 0.04], higher mean right atrial pressure and lower LVEF were independent predictors of death. Conclusions: In severe AS patients, lower MAP reflects lower systemic vascular resistance and valvulo‐arterial impedance, which may help to preserve stroke volume and filling pressures despite reduced left ventricular performance, and lower MAP is a predictor of higher long‐term post‐AVR mortality.